1992
DOI: 10.1002/bit.260400706
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of cloned genes using recombinant Escherichia coli regulated by a T7 promoter: I. Batch cultures and kinetic modeling

Abstract: A novel Eschericha coli expression system directed by bacteriophage T7 RNA Polymerase utilized for overexpression of the cloned gene. The recombinant cell contains the plasmid with a bacteriophage promoter, the T7 promoter, to regulate the expression of the target gene. This promoter is recognized only by T7 RNA polymerase, whose gene has been fused into the host chromosome and is under control of the lacUV5 promoter. Therefore, the target gene on the plasmid can be expressed only in the presence of T7 RNA pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 10 publications
1
17
1
1
Order By: Relevance
“…Generally, it is well established that IPTG induction can decrease cell growth. 18,19 However, the opposite effect was observed in our assays with M15. A variation of the correlation g DCW/OD 600 nm was identified as an explanation for this incongruence.…”
Section: Rhua Over-expression In Shake Flask Cultivationscontrasting
confidence: 64%
“…Generally, it is well established that IPTG induction can decrease cell growth. 18,19 However, the opposite effect was observed in our assays with M15. A variation of the correlation g DCW/OD 600 nm was identified as an explanation for this incongruence.…”
Section: Rhua Over-expression In Shake Flask Cultivationscontrasting
confidence: 64%
“…This showed that our measurement data was accurate when compared with the representation proposed here. However, with respect to process optimization, the approach [13] requires additional state variables and more complex kinetics to avoid unrealistic control profiles. The latter tend to maintain a specific biomass growth rate in the protein production phase close to zero.…”
Section: Model Descriptionmentioning
confidence: 99%
“…This approach can be considered as a form of self-inhibition effect [13]. However, we assume that the maximal specific product concentration value p max , approached asymptotically, to be dependent on l. p max was observed to decrease with higher biomass growth rates l, but is expected to be very low when the specific biomass growth rate l approaches zero.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been few reports of foreign production models that consider induction effects (Bentley et al, 1991;Betenbaugh and Dhurjati, 1990;Lee and Ramirez, 1992;Miao and Kompala, 1992). Lee and Ramirez (1992) proposed a mathematical model that included inducer effects on cell growth and foreign protein production.…”
Section: Model Developmentmentioning
confidence: 99%